2017
DOI: 10.1111/mec.14022
|View full text |Cite
|
Sign up to set email alerts
|

Purging putative siblings from population genetic data sets: a cautionary view

Abstract: Interest has surged recently in removing siblings from population genetic data sets before conducting downstream analyses. However, even if the pedigree is inferred correctly, this has the potential to do more harm than good. We used computer simulations and empirical samples of coho salmon to evaluate strategies for adjusting samples to account for family structure. We compared performance in full samples and siblingreduced samples of estimators of allele frequency (P), population differentiation (F ST ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 38 publications
5
143
0
2
Order By: Relevance
“…Many researchers have concluded that it is important to remove putative siblings from population genetics datasets before conducting downstream analyses (Corlett, 2017; Johnson et al., 2016), but there are several good reasons why this can create more problems than it solves (Waples & Anderson, 2017). First, siblings occur naturally in all natural populations, at frequencies that are inversely related to effective population size; therefore, removing siblings erases signals characteristic of small populations and makes the populations appear to be larger.…”
Section: Genotyping Error and Improving Data Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have concluded that it is important to remove putative siblings from population genetics datasets before conducting downstream analyses (Corlett, 2017; Johnson et al., 2016), but there are several good reasons why this can create more problems than it solves (Waples & Anderson, 2017). First, siblings occur naturally in all natural populations, at frequencies that are inversely related to effective population size; therefore, removing siblings erases signals characteristic of small populations and makes the populations appear to be larger.…”
Section: Genotyping Error and Improving Data Qualitymentioning
confidence: 99%
“…As shown by Waples and Anderson (2017), however, performance of the BLUE also depends on having accurate pedigree information. When sample identification is not reliable, the use of the full dataset outperforms BLUE.…”
Section: Genotyping Error and Improving Data Qualitymentioning
confidence: 99%
“…Variability in N e estimates has been linked to differences in reproductive success and/or the methods used in their computation (Hare et al, 2011;Waples et al, 2013Waples et al, , 2014Coscia et al, 2016;Waples and Anderson, 2017). For example, Waples et al (2014) demonstrated that N e estimates based on a variety of age-structured samples are likely to be underestimated due to Wahlund effects.…”
Section: Effective Population Size and Population Bottlenecksmentioning
confidence: 99%
“…For many population genetic parameters (category II monitoring in Schwartz et al, 2007) sampling should be designed to be random with respect to kin (this can also be addressed by post hoc data pruning, but see Waples & Anderson, 2017). …”
Section: Sampling Issuesmentioning
confidence: 99%